Genetic variation in intraspecific populations of Rabdophaga rosaria (Diptera: Cecidomyiidae) indicating possible diversification scenarios into sibling species along with host range expansion on willows (Salicaceae: Salix). Issue 4 (20th February 2020) - Sato, Shinsuke; Harris, Keith M; Collet, Dominique M; Kim, Wanggyu; Yukawa, Junichi
Abstract: We analysed the COI gene of mitochondrial DNA extracted from larvae of Rabdophaga (Diptera: Cecidomyiidae) that induce rosette galls on Salix in the Holarctic Region. Genetic data show that they belong to species groups of Rabdophaga rosaria and Rabdophaga strobiloides . A maximum likelihood tree indicates that R. rosaria and R. strobiloides populations are divided into clades 1 and 2, respectively. Clade 1 is divided into subclades 1 and 2, and the latter is further divided into subclades 2A and 2B. Subclade 1 consists of populations on several Salix species of section Cinerella in subgenus Vetrix in Georgia and the UK. Subclade 2A contains populations on Salix alba (section Salix, subgenus Salix ) in The Netherlands and the UK. Subclade 2B consists of populations on section Helix in Poland, Phylicifoliae in Alaska and Salix species in the Eastern Palaearctic Region. The genetic differences between populations of subclades 1, 2A and 2B range from 1.06 to 3.46%. We propose a possible diversification scenario of R. rosaria into sibling species through the expansion of host plant ranges. Clade 2 consists of R. strobiloides populations on two Alaskan Salix species of the sections Hastatae and Sitchenses in subgenus Vetrix .